Memorandum on the Use of Information Technology to Improve Medication Safety - Ammenwerth, E.; Aly, A.-F.; Bürkle, T.; Christ, P.; Dormann, H.; Friesdorf, W.; Haas, C.; Haefeli, W. E.; Jeske, M.; Kaltschmidt, J.; Menges, K.; Möller, H.; Neubert, A.; Rascher, W.; Reichert, H.; Schuler, J.; Schreier, G.; Schulz, S.; Seidling, H. M.; Stühlinger, W.; Criegee-Rieck, M. (Methods of Information in Medicine, 2014)
Background: Information technology in health care has a clear potential to improve the quality and efficiency of health care, especially in the area of medication processes. On the other hand, existing studies show possible adverse effects on patient safety when IT for medication-related processes is developed, introduced or used inappropriately.Objectives: To summarize definitions and observations on IT usage in pharmacotherapy and to derive recommendations and future research priorities for decision makers and domain experts.Methods: This memorandum was developed in a consensus-based iterative process that included workshops and e-mail discussions among 21 experts coordinated by the Drug Information Systems Working Group of the German Society for Medical Informatics, Biometry and Epidemiology (GMDS).Results: The recommendations address, among other things, a stepwise and comprehensive strategy for IT usage in medication processes, the integration of contextual information for alert generation, the involvement of patients, the semantic integration of information resources, usability and adaptability of IT solutions, and the need for their continuous evaluation.Conclusion: Information technology can help to improve medication safety. However, challenges remain regarding access to information, quality of information, and measurable benefits.
Keywords: Drug therapy safety; information technology; medication safety; decision support systems; drug safety; patient safety